Fungsi SDM Sebagai Pemain Strategik Manajemen Modal Insani dan Manajemen Talenta - Fareiz Aulia Firman; Dr. Vip Paramarta Drs., MM; Rocky Fransiskus Budiman; Yuliani Salewe; Karlis Karlis (Journal of Creative Student Research, 2023)
Human resource management (HR) has a very important role in managing human capital and talent management in organizations. The presence of qualified and professional human resources can become strategic players in achieving organizational goals and improving individual and collective performance. This study aims to examine the function of HR as a strategic player in human capital management and talent management. This study uses a qualitative descriptive research method by collecting data through interviews, observation, and analysis of related documents. Respondents to this study were HR managers, employees and team leaders working in various companies in the private sector. The collected data were then analyzed using a thematic approach. The results of the study show that the function of HR as a strategic player in human capital management includes the process of recruitment, selection and appropriate placement, competence development, performance management, as well as coaching and fair rewards. Good human resources can help organizations manage human capital effectively, increase productivity, and build a positive organizational culture. In addition, the function of HR as a strategic player in talent management involves identifying and developing individual potential, creating clear career paths, managing knowledge and experience, and leadership development programs. Human resources who are able to manage and utilize existing talent will help the organization face the challenges of intense competition and ensure long-term sustainability.